2006
DOI: 10.1021/pr060327k
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis Plasma Protein Profiling with Immunodepletion, Three-Dimensional Liquid Chromatography Tandem Mass Spectrometry, and Spectrum Counting

Abstract: Sepsis is a systemic, often fatal inflammatory response whose biochemical pathways are not fully understood and with no single biomarker capable of its reliable prediction. Increased interest in protein profiling to reveal fundamental biochemical events as well as disease diagnosis has grown considerably, largely due to advances in mass spectrometry and related front-end technologies. In this study, patients with sepsis and systemic inflammatory response syndrome (SIRS) were examined using plasma protein profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 37 publications
5
42
0
Order By: Relevance
“…Experiment 1 evaluated proteins differentially expressed at all time points tested between preseptic SIRS and uninfected SIRS in pooled plasma samples using a three-dimensional reverse phase/strong cation exchange/reverse phase liquid chromatography (LC 3 ) with electrospray ion trap mass spectrometry (MS 2 ), and spectrum counting for comparative quantitation 14 (performed by Mass Consortium Corporation, San Diego, CA). Briefly, plasma samples from 18 preseptic patients and 17 SIRS patients were pooled into 6 plasma pools (3 preseptic and 3 uninfected SIRS).…”
Section: Methodsmentioning
confidence: 99%
“…Experiment 1 evaluated proteins differentially expressed at all time points tested between preseptic SIRS and uninfected SIRS in pooled plasma samples using a three-dimensional reverse phase/strong cation exchange/reverse phase liquid chromatography (LC 3 ) with electrospray ion trap mass spectrometry (MS 2 ), and spectrum counting for comparative quantitation 14 (performed by Mass Consortium Corporation, San Diego, CA). Briefly, plasma samples from 18 preseptic patients and 17 SIRS patients were pooled into 6 plasma pools (3 preseptic and 3 uninfected SIRS).…”
Section: Methodsmentioning
confidence: 99%
“…Spectral counting has been established as a reliable method for both relative (38,41) and absolute (39, 46) quantification of proteins based on LC-MS/MS data. Comparison of raw spectral counts has previously been used for relative quantification between plasma samples (47). Here, following a simplification of the APEX method of Lu and coworkers (39), we obtain absolute quantification by normalizing spectral counts to adjust for the number of observable tryptic peptides per protein and by calibrating to previously measured protein concentrations.…”
Section: Choice Of Atlas Stringency Level For Analysis)mentioning
confidence: 99%
“…Our previous studies and those of others have shown that the combination of LC with electrospray-ionization mass spectrometry (ESI-MS), abbreviated LC-MS, is suitable to analyze body fluids such as serum or urine [9,10]. The increasing number of applications of LC-MS and LC-MS-MS for the profiling of body fluids or the targeted detection of individual proteins underscores furthermore that this method is capable of achieving concentration sensitivities in the ng-pg/mL range [11][12][13][14][15][16][17][18]. In return, LC-MS provides highly complex data sets when used in the profiling mode (measurement of all detectable compounds in a sample) and it is thus not easy to assess the effect of a given pre-analytical parameter on the overall result.…”
Section: Introductionmentioning
confidence: 99%